Effect of Caffeine and Flavonoids on the Binding of Tigecycline to Human Serum Albumin: A Spectroscopic Study and Molecular Docking - Miroslav Sovrlić; Emina Mrkalić; Ratomir Jelić; Marina Ćendić Serafinović; Stefan Stojanović; Nevena Prodanović; Jovica Tomović (MDPI AG, 2022)
Human serum albumin (HSA) has a very significant role in the transport of drugs, in their pharmacokinetic and pharmacodynamic properties, as well as the unbound concentration of drugs in circulating plasma. The aim of this study was to look into the competition between tigecycline (TGC) and alkaloid (ALK) (caffeine (CAF)), and flavonoids (FLAVs) (catechin (CAT), quercetin (QUE), and diosmin (DIO)) in binding to HSA in simulated physiological conditions using multiple spectroscopic measurements and docking simulations. Fluorescence analysis was used to find the binding and quenching properties of double HSA-TGC and triple HSA-TGC-CAF/FLAV systems. The conformational change of the HSA was analyzed using synchronous fluorescence spectroscopy, Fourier transform infrared spectroscopy, and circular dichroism. Obtained results of spectroscopic analyses indicate that triple complexes of HSA-TGC-CAF/FLAVs are formed without problems and have higher binding affinities than double HSA-TGC. In addition, TGC does not change the microenvironments around the tryptophan (Trp) and tyrosine (Tyr) residues in the presence of ALK and FLAVs. Ultimately, the binding affinity, competition, and interaction nature were explored by docking modeling. Computational outcomes are in good accordance with experimentally obtained results. Accordingly, concluding remarks may be very useful for potential interactions between common food components and drugs.